2017
DOI: 10.3390/hydrology4010013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Global Reanalysis Datasets as Input for Hydrological Modelling in the Sudano-Sahel Region

Abstract: This paper investigates the potential of using global reanalysis datasets as input for hydrological modelling in the data-scarce Sudano-Sahel region. To achieve this, we used two global atmospheric reanalyses (Climate Forecasting System Reanalysis and European Center for Medium-Range Weather Forecasts (ECMWF) ERA-Interim) datasets and one global meteorological forcing dataset WATCH Forcing Data methodology applied to ERA-Interim (WFDEI). These datasets were used to drive the Soil and Water Assessment Tool (SWA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…Andersson et al (2015) used WFDEI as input to drive Hydrological Prediction of the Environment (HYPE) across different basins in Europe and Africa and concluded that, this dataset improved streamflow simulation compared to Watch Forcing Data (WFD) based on ERA-40. In a previous study Nkiaka et al (2017), compared the performance of CFSR, ERA-Interim and WFDEI for hydrological modelling in the Logone catchment and concluded that, WFDEI outperformed the other two datasets in simulating streamflow.…”
Section: Meteorological Datamentioning
confidence: 99%
“…Andersson et al (2015) used WFDEI as input to drive Hydrological Prediction of the Environment (HYPE) across different basins in Europe and Africa and concluded that, this dataset improved streamflow simulation compared to Watch Forcing Data (WFD) based on ERA-40. In a previous study Nkiaka et al (2017), compared the performance of CFSR, ERA-Interim and WFDEI for hydrological modelling in the Logone catchment and concluded that, WFDEI outperformed the other two datasets in simulating streamflow.…”
Section: Meteorological Datamentioning
confidence: 99%
“…Previously, the hydrological model was calibrated with interpolated in situ precipitation data at 1 km resolution. Some previous studies calibrated the model for each precipitation dataset to evaluate the sensitivity of model parameters to precipitation (Andréassian et al, 2001;Nkiaka et al, 2017). In this study, model parameters are not optimized for each forcing aiming to avoid correcting precipitation errors through fine-tuning the hydrological processes representation in the model (sensitivity analysis).…”
Section: Hydrological Modeling and Discharge Evaluationmentioning
confidence: 99%
“…), the hydrological model structure (Koren et al, 1999) and the considered spatial and time scales (Segond et al, 2007). Some studies stated that the impact of precipitation spatial resolution on discharge simulation was not significant (Gascon et al, 2015;Nkiaka et al, 2017). However, most studies (Andréassian et al, 2001;Smith et al, 2004;Schuurmans and Bierkens, 2006;Wagener et al, 2007;Arnaud et al, 2011;Fu et al, 2011;Zoccatelli et al, 2011;Emmanuel et al, 2012;Zhao et al, 2013;Lobligeois et al, 2014) showed that better model performances were obtained when representation of the spatial variability of precipitation was improved.…”
Section: Introductionmentioning
confidence: 99%
“…We recently investigated the science–policy interface as part of research into the impact of climate and hydrological changes on social and ecological vulnerability in the Lake Chad Basin (Nkiaka, Nawaz & Lovett, ,b, ,b). Our concern was that research often does not contribute to policy development that can solve societal problems, and there appears to be two parallel lines that do not intersect.…”
mentioning
confidence: 99%